Muslim Spain reconsidered from 711 to 1502 - Hitchcock, Richard (New Edinburgh Islamic surveys, 2014)
What made Muslim Spain a unique and successful society? Richard Hitchcock explores the background to its powerful legacy in the formation of modern Spain, using a chronological framework while constantly keeping in view the shifting social patterns caused by the changing balance between town and country, major and minor dynasties, foreign groupings and repeated invasions from North Africa. You'll learn about the main historical developments in depth, such as the self-defeating independence of the Taifas, the so-called 'Party Kings', and the prolonged colonisation of the Muslim subject population under the increasingly severe dominance of the Kingdoms of Aragon and Castile. You'll also find wide-ranging discussion of important topics such as inter-faith relations, multi-ethnic competing groups and how intellectual life was enriched by pluralism and influences from abroad. --Provided by publisher